2021
DOI: 10.1111/trf.16444
|View full text |Cite
|
Sign up to set email alerts
|

Screening for new red blood cell alloantibodies after transfusion in patients with sickle cell disease

Abstract: Background Patients with sickle cell disease (SCD) are frequent recipients of red blood cell (RBC) transfusions and are at risk for RBC alloimmunization. RBC alloimmunization is diagnosed by identifying RBC alloantibodies as part of pre‐transfusion testing, but this testing fails to detect alloantibodies that have evanesced. It may be beneficial to screen for new RBC alloantibody development after transfusion before possible antibody evanescence. Study Design and Methods Our institution started a new initiativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 74 publications
(137 reference statements)
0
13
0
Order By: Relevance
“…Stack et al estimated that only about 30% of new RBC alloantibodies are detected clinically through current antibody screening practices 25 . Among paediatric patients with SCD, we found that historically fewer than 18% of patients had an antibody screen obtained 2–6 months after transfusion 26 . While not generally standard of care, it has been proposed that all transfused patients should have a follow‐up antibody screen after a RBC transfusion 27 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Stack et al estimated that only about 30% of new RBC alloantibodies are detected clinically through current antibody screening practices 25 . Among paediatric patients with SCD, we found that historically fewer than 18% of patients had an antibody screen obtained 2–6 months after transfusion 26 . While not generally standard of care, it has been proposed that all transfused patients should have a follow‐up antibody screen after a RBC transfusion 27 .…”
Section: Discussionmentioning
confidence: 81%
“…27 At our institution we recently showed that such screening is feasible, but it appears to be low yield in terms of detecting new alloantibodies in patients with SCD transfused C/E/K matched RBCs. 26 Even if this patient's anti-E alloimmunization had been previously diagnosed at his primary institution, this information would not have been documented at our hospital. Obtaining complete blood bank records is difficult given the lack of a national transfusion database.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This could include routine repeat type and screen, DAT, hemoglobin studies and CBCs at the time of presentation for any SCD complications or for routine evaluation of alloimmunization within a month of transfusion, even in the absence of symptoms. One study showed minimal benefit to routine screening 2–6 months post‐transfusion when the patients were CEK‐matched 38 . However, it is possible that antibodies have evanesced by that time frame.…”
Section: Investigating the Frequency And Causes Of Dhtrs In Scd Patie...mentioning
confidence: 99%
“…One study showed minimal benefit to routine screening 2-6 months post-transfusion when the patients were CEK-matched. 38 However, it is possible that antibodies have evanesced by that time frame. Therefore, we recommend routine, standard of care testing for alloantibodies within 1 month of transfusion.…”
Section: Nhsn Redefinition Of Dhtr Diagnosismentioning
confidence: 99%